Overview of religious freedom in Ukraine, including Crimea - Vasin, Maksym (Relihijna svoboda, 2016)
In Ukraine, believers of all faiths can exercise freedom of religion to a sufficient degree. Despite the fact that the Law of Ukraine "On Freedom of Conscience and Religious Organizations" has not been substantially revised since 1991 and needs to be improved in the context of social transformations, favorable conditions for the development and annual growth of the number and diversity of religious organizations have been formed on its basis.